Litteraturvetenskapliga perspektiv : på begreppet hållbar utveckling - Hemmilä, Olavi (Tidskrift för litteraturvetenskap, 2010)
Sustainability and the Uses of Fiction In 1987 the United Nations agreed upon the now well-known followingdefinition of the term sustainability: »Sustainable development seeks tomeet the needs and aspirations of the present without compromising theability to meet those of the future. «In The Idea of Justice (2009), Amartya Sen suggests that this term shouldbe understood in a wider context: »Certainly, people do have needs, butthey also have values and, in particular, cherish their ability to reason,appraise, choose, participate and act.« Taking these general positions asa starting point, this study discusses narrative strategies employed innovels by the Finnish authors Arto Paasilinna and Johanna Sinisalo (in theso called »ecothriller« genre) and in various forms of »toxic discourses«(exemplified by travelogues focusing on the Falun mine in Sweden and inPhaedra C. Pezzullo’s book Toxic Tourism). The theoretical basis for thestudy is ecocriticism, a new field of research which studies the relationbetween texts and the physical world. The article concludes that the formation of a sustainable society is to alarge extent the result of conscious choices between alternative ways oftelling stories about the world. Highlighting the dynamics of ourrelationship with the physical environment is an essential contributionfrom the humanities to the formation of a sustainable society.